Multidimensional Transition Metal Complexes Based on 3-Amino-1H-1,2,4-triazole-5-carboxylic Acid: From Discrete Mononuclear Complexes to Layered Materials - Liu, Bing (2017)
The synthesis and structural characterization of five transition metal complexes with different dimensionality and incorporating residues of 3-amino-1H-1,2,4-triazole-5-carboxylic acid (H(2)atrc) is reported: [Zn(Hatrc)(2)(H2O)] (1), [Mn(Hatrc)(2)(H2O)(2)]center dot 2H(2)O (2), [Fe-2(Hatrc)(4)(OH)(2)]center dot 6H(2)O (3), [Cd(Hatrc)(2)(H2O)](n) (4), and [Mn(atrc)(H2O)](n)center dot nH(2)O (5). These materials could be prepared from solution (1-3), diffusion (4), or hydrothermal reactions (5) with various anions and L:M ratios. Structural details were revealed by single crystal X-ray diffraction. The discrete units composing compounds 1-3, the polymeric 1D chain of 4 and the 2D layer of 5 are further extended into 3D supramolecular architectures through the formation of hydrogen bonds.